Data of a sub-analysis of the DEMDATA study: characteristics of Austrian and Czech nursing homes residents - Höfler, Margit; Ratajczak, Paulina; Beránková, Anna; Prieschl, Doris; Šteffl, Michal; Holmerová, Iva; Auer, Stefanie R (BMC research notes, 2019)
OBJECTIVES: The aim of this data paper is to provide the data set of a sub-analysis of the DEMDATA study data. In the DEMDATA study, epidemiological data on the prevalence and severity of dementia, as well as functioning, behavioral problems and other health related factors in residents living in Austrian and Czech nursing homes were collected. The DEMDATA project further provides information on relatives' perception of the life Quality of residents, care team burden as well as environmental factors. Participating nursing homes were randomly drawn and stratified. Inclusion criteria for participation were that the resident was living permanently in the institution and that he/she and/or a legal representative (where relevant) had signed an informed consent. DATA DESCRIPTION: This paper provides data of cognitive, functional and behavioral assessments as well as other health related information of 1085 residents living in Austrian and Czech nursing homes. For each resident, several measurements on his or her cognitive, functional, and behavioral status are available. Also further health-related factors such as quality of life, pain, numbers of falls and hospital stays are provided.
Keywords: testy pro posouzení mentálních funkcí a demence; Nursing homes; Nursing Homes; Humans; demence; Quality of Life; prevalence; Female; Aged; senioři; lidé; Rakousko; kvalita života; Epidemiological data; Austria; ženské pohlaví; Male; Czech Republic; Aged, 80 and over; Dementia; Cross-Sectional Studies; Prevalence; senioři nad 80 let; Mental Status and Dementia Tests; Homes for the Aged; Česká republika; mužské pohlaví; domovy pro seniory; průřezové studie; pečovatelské domovy